Sex(ism) doesn't sell: Disentangling the effects of nudity and sexism in advertising - Mira Hertel; Laura Palla; Hans-Georg Wolff (Acta Psychologica)
Though advertisers frequently use sex appeal to improve advertising effectiveness, its effects on recipients' attitudes are not fully understood. In fact, a recent meta-analysis by Wirtz et al. (2018) reports heterogeneous effect sizes and suggests that differences among sexual stimuli might contribute to this heterogeneity. We adopt this proposition and argue that while scholars mostly use nudity to manipulate sex appeal in advertising, these manipulations often confound nudity and sexism. We seek to disentangle unique and interactive effects of nudity and sexism on attitudes towards the ad and the brand. We conduct two preregistered experiments using 16 real and fictitious print ads of female models, respectively. Through an orthogonal manipulation of nudity and sexism, we provide a rigorous estimation of the independent effect sizes and show that effects of nudity are small, whereas sexism exerts medium to strong effects on attitudes. Therefore, sexism rather than nudity appears to drive consumers' negative responses.